The efficacy and safety of continuous theta burst stimulation for auditory hallucinations: a systematic review and meta-analysis of randomized controlled trials - Ye, Shi-Yi; Chen, Chun-Nuan; Wei, Bo; Zhan, Jin-Qiong; Li, Yi-Heng; Zhang, Chen; Huang, Jing-Jing; Yang, Yuan-Jian (Frontiers in Psychiatry, 2024)
Objective: Auditory hallucinations are the most frequently occurring psychotic symptom in schizophrenia. Continuous theta burst stimulation (cTBS) has been used as an adjuvant treatment for auditory hallucinations. This meta-analysis focused on randomized controlled clinical trials (RCTs) to assess the efficacy of adjuvant cTBS on auditory hallucinations in schizophrenia. Methods: We performed a comprehensive search of four international databases from their inception to January 14, 2024, to identify relevant RCTs that assessed the effects of adjuvant cTBS on auditory hallucinations. The key words included “auditory hallucinations”, “continuous theta burst stimulation” and “transcranial magnetic stimulation”. Inclusion criteria included patients with auditory hallucinations in schizophrenia or schizoaffective disorder. The Revised Cochrane risk-of-bias tool for randomized trials (RoB1) were used to evaluate the risk of bias and the Review Manager Software Version 5.4 was employed to pool the data. Results: A total of 4 RCTs involving 151 patients with auditory hallucinations were included in the analysis. The Cochrane risk of bias of these studies presented “low risk” in all items. Preliminary analysis showed no significant advantage of adjuvant cTBS over sham stimulation in reducing hallucinations [4 RCTs, n = 151; SMD: -0.45 (95%CI: -1.01, 0.12), P = 0.13; I2 = 61%]. Subgroup analysis revealed that patients treated with adjuvant cTBS for more than 10 stimulation sessions and total number of pulses more than 6000 [3 RCTs, n = 87; SMD: -4.43 (95%CI: -8.22, -0.63), P = 0.02; I2 = 47%] had a statistically significant improvement in hallucination symptoms. Moreover, the rates of adverse events and discontinuation did not show any significant difference between the cTBS and sham group. Conclusions: Although preliminary analysis did not revealed a significant advantage of adjuvant cTBS over sham stimulation, subgroup analysis showed that specific parameters of cTBS appear to be effective in the treatment of auditory hallucinations in schizophrenia. Further large-scale studies are needed to determine the standard protocol of cTBS for treating auditory hallucinations.